Graphic practices and literacies in the history of English - Peikola, Matti; Tyrkkö, Jukka; Varila, Mari-Liisa 1984- (Brepols, 2025)
"Graphic devices such as tables and diagrams and other visual strategies of organising text and information are an essential part of communication. The use of these devices and strategies in books and documents developed throughout the medieval and early modern periods, as knowledge was translated and circulated in European vernaculars. Yet the use of graphic practices and multimodal literacies associated with them have mostly been examined in the context of Latin, Greek, Arabic, and Hebrew, and early vernacular writing remains an under-researched area. This volume brings together contributors from English historical linguistics and book studies to highlight multimodal graphic practices and literacies in texts across a range of genres and text types from the late medieval period until the eighteenth century. Contributions in the volume investigate both handwritten and printed materials, from books in the domains of medicine, religion, history, and grammar, to administrative records and letter writing."
Literaturverzeichnis Seite [311]-340. - Index
"This book grew out of the 2021 workshop 'Graphic literacy in the history of English' we organised in the 21st International Conference on English Historical Linguistics in Leiden. In addition to chapters developed from papers given in the workshop, the volume also contains other invited contributions by experts in the field [...]" -- Acknowledgements
Keywords: Englisch; Kommunikation; Multimodalität; Historische Sprachwissenschaft; Grafik; Konferenzschrift -- 2021 -- Leiden